Training volume, intensity, and performance of world-class Chinese rowers prior to the 2019 World Championships: A case study - Zhong, Y.; Zheng, H.; Weldon, A.; Nugent, F.; Gee, T. I.; Sperlich, B.; Moore, D.; Zi, W.; Li, Y. (International Journal of Sports Science & Coaching, 2025)
Six world-class Chinese male rowers (age: 28.2 ± 3.2 years; height: 1.93 ± 0.02 m; body mass: 94.7 ± 3.9 kg) participated in the study. The training volume in different modalities and intensities were recorded over 44 weeks. To evaluate rowing performance, rowers completed four 2000 m and 5000 m maximum effort time trials and two incremental step tests. Total training time for the season was 907 h, which consisted of 67.5% of rowing training, 16.9% of strength training, 15.2% of warm-up and flexibility, and 0.4% of non-specific endurance training. The rowing training intensity distribution (TID) was 87.0% performed at low intensity (LIT), 8.4% at moderate intensity (MIT), and 4.6% at high intensity (HIT). There was no significant difference in average weekly rowing training volume (distance) at LIT across four phases (p = 0.12), as well as rowing training at MIT (p = 0.07) and HIT (p = 0.97). The fourth 2000 m time trials performance significantly improved from the first trial (-6.4 s, p = 0.02). The fourth 5000 m time trial performance was significantly improved from the first (-13.4 s, p = 0.02) and second trial (-14.1 s, p = 0.01). The final-step mean power output (W) in the second incremental step test improved significantly (p = 0.04). In the 2018-19 season, China's world-class rowers conducted considerable LIT rowing. The training volume distribution and rowing TID were similar in all phases.